Literature Review of Biolarvacide Testing from Gadung Tuber (Dioscorea hispida) for Aedes aegypti Mosquito Larvae - Risma Mawardah (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
Efforts to prevent the dengue virus, which is transmitted by the Aedes aegypti mosquito with vegetable larvicides, have not been maximally utilized. Gadung tuber (Dioscorea hispida) is a type of plant that has high potential as vegetable larvicides because it contains HCN toxins. This literature review aims to determine the concentration of gadung tuber extract which is effective for larvicide against the mortality of Aedes aegypti mosquito larvae. The independent variable in this literature review is the concentration of gadung tubers (Dioscorea hispida) and the dependent variable is the mortality of Aedes aegypti mosquito larvae. The article was obtained from Google Scholar, using the keyword "Larvicide from gadung tubers in Aedes mosquito larvae". Inclusion criteria for journals indexed by Sinta S1-S6 or with ISSN, experimental research methods, research in the last 10 years, and in Indonesian. The method used is to summarize the five selected journals, analyze, and draw conclusions. The conclusion of the five journals is that the lowest most effective concentration to be used for Aedes aegypti mosquito larva biolarvicide is 0.07% with LC90. This shows that the extract of gadung tuber (Dioscorea hispida) is effective as a biolarvicide against the death of Aedes aegypti mosquito larvae. Utilization of the potential of gadung tubers as biolarvicides can reduce environmental pollution without disturbing other ecosystems and implementing healthy living. Suggestions for further research should be to use multilevel concentrations, make sure to choose the age of the gadung tubers, the different types of gadung tubers used, the place of origin for the gadung tubers to be taken, and the content contained in the soil where the gadung tubers are grown before doing the research, and it is necessary to examine other parts of the plant gadung other than tubers.